EFEKTIFITAS PEMBELAJARAN SUHU DAN KALOR MENGGUNAKAN MODEL INKUIRI TERBIMBING DISERTAI MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Ilvi Maulida Nurdiana; Alex Harijanto; Sri Handono Budi (JURNAL PEMBELAJARAN FISIKA, 2019)
This study aims to (1) determine the level of students’ critical thinking skill after learning using guided inquiry model with Mind Mapping techniques; (2) to assess the effectiveness of learning temperature and heat using guided inquiry learning model with Mind Mapping techniques towards students’ critical thinking skill. The type of this study was descriptive along with one group Pre-test Post-test research design. This research was conducted in one of Senior High Schools in Jember. The population of this study was all students from grade XI IPA and class XI IPA 3 consists of 33 students was the sample of this study. The data collection technique was test, interview, and documentation. The data analysis technique of critical thinking skill used the percentage of post-test score which was gotten, and the analysis of learning effectiveness used normalized N-Gain test to determine the improvement of students’ critical thinking skill. The result showed that the improvement of students’ critical thinking skill increased after the learning with average score 82, 73 which was categorized as high. And the data analysis of learning effectiveness showed N-gain score was 0, 7453 and was categorized as high level as well. It can be concluded that after the learning was done using guided inquiry learning model with Mind Mapping techniques, the level of students’ critical thinking skill is high and this model is effective to be applied to increase critical thinking skill of Senior High School students.Keyword: learning effectiveness, guided inquiry model, critical thinking skill